Application of Thermal Spray Coatings in Electrolysers for Hydrogen Production: Advances, Challenges, and Opportunities. Issue 12 (8th November 2022) - Faisal, Nadimul Haque; Prathuru, Anil; Ahmed, Rehan; Rajendran, Vinooth; Hossain, Mamdud; Venkatachalapathy, Viswanathan; Katiyar, Nirmal Kumar; Li, Jing; Liu, Yuheng; Cai, Qiong; Horri, Bahman Amini; Thanganadar, Dhinesh; et al.
Abstract: Thermal spray coatings have the advantage of providing thick and functional coatings from a range of engineering materials. The associated coating processes provide good control of coating thickness, morphology, microstructure, pore size and porosity, and residual strain in the coatings through selection of suitable process parameters for any coating material of interest. This review consolidates scarce literature on thermally sprayed components which are critical and vital constituents (e. g., catalysts (anode/cathode), solid electrolyte, and transport layer, including corrosion‐prone parts such as bipolar plates) of the water splitting electrolysis process for hydrogen production. The research shows that there is a gap in thermally sprayed feedstock material selection strategy as well as in addressing modelling needs that can be crucial to advancing applications exploiting their catalytic and corrosion‐resistant properties to split water for hydrogen production. Due to readily scalable production enabled by thermal spray techniques, this manufacturing route bears potential to dominate the sustainable electrolyser technologies in the future. While the well‐established thermal spray coating variants may have certain limitations in the manner they are currently practiced, deployment of both conventional and novel thermal spray approaches (suspension, solution, hybrid) is clearly promising for targeted development of electrolysers. Abstract : This is an extensive review on the application of thermally sprayed coatings with functional properties for electrolysers. Such coatings are critical and vital constituents (as catalysts (anode/cathode), solid electrolyte, and transport layer, including corrosion‐prone parts such as bipolar plates) of the water splitting electrolysis process for hydrogen production.